Bàn về dịch văn ngôn Trung Quốc sang tiếng Việt = Useful skills and suggestions for the translation of ancient Chinese into Vietnamese /Nguyễn Ngọc Lân - Nguyễn, Ngọc Lân
Literary Chinese is written language originated from ancient Chinese spoken language. Previously, Literary Chinese was used in official documents not only in China but also in countries under the influence of sinology, namely North Korea, Japan and Vietnam. Through the analysis of the difficulties frequently encountered in the Literary Chinese-Vietnamese translation process, this article will address some methods and techniques for translating Literary Chinese in order to improve the quality and effectiveness of the translation, thus, facilitate learners’ study and research on Literary Chinese.